2020
DOI: 10.3390/ijms21218133
|View full text |Cite
|
Sign up to set email alerts
|

Viruses in Cancers of the Digestive System: Active Contributors or Idle Bystanders?

Abstract: The human virome, which is a collection of all the viruses that are present in the human body, is increasingly being recognized as an essential part of the human microbiota. The human gastrointestinal tract and related organs (e.g., liver, pancreas, and gallbladder)—composing the gastrointestinal (or digestive) system—contain a huge number of viral particles which contribute to maintaining tissue homeostasis and keeping our body healthy. However, perturbations of the virome steady-state may, both directly and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 229 publications
1
14
0
1
Order By: Relevance
“…Changes in the fecal virome, especially the phage population, have been reported recently for CRC patients [7,65,73,90]. It has been suggested that phages may play a causative role in CRC by altering the bacterial populations of the intestine such that pathogenic bacteria can thrive and form biofilms [72,73] (Figure 1B).…”
Section: The Human Intestinal Virome and Its Links To Cancermentioning
confidence: 63%
See 3 more Smart Citations
“…Changes in the fecal virome, especially the phage population, have been reported recently for CRC patients [7,65,73,90]. It has been suggested that phages may play a causative role in CRC by altering the bacterial populations of the intestine such that pathogenic bacteria can thrive and form biofilms [72,73] (Figure 1B).…”
Section: The Human Intestinal Virome and Its Links To Cancermentioning
confidence: 63%
“…The proposed mechanisms of viral contributions to carcinogenesis also vary widely between viral species and will be briefly discussed in the following subsections. In general, viral infections can contribute to carcinogenesis by any of the following mechanisms: insertional mutation in the host genome, induction of inflammation and modulation of signaling pathways in the infected cells, for example, by viral oncogenes [6,7] (Figure 1A).…”
Section: The Roles Of the Eukaryotic Virome In Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Viral infections including HPV, Epstein-Barr virus (EBV), hepatitis B and C viruses, human T-lymphotropic virus-1, and polyomaviruses are considered as the major risk factor for about 20% of all cancers (4)(5)(6). Thus, some studies proposed a possible link between viruses such as EBV, HPV, and cytomegalovirus (CMV) with esophageal carcinoma (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%